Perception Towards Joint Forest Management Programme in Conservation of Forest Resources in Jammu Division (Indian Journal of Extension Education, 2021)
The present study was conducted in purposively selected “East Forest Circle” of Jammu division of J&K. Multistage sampling plan was followed for the selection of respondents. Six forest ranges from East circle having maximum number of JFMCs were selected purposively. Twenty four committees, four from each selected ranges of East circle and eight members from each selected JFMC were selected through random sampling technique making the sample size to 192 respondents. The perception measurement consisted of 26 items. Results of quasi- experimental research design showed that majority of JFMC’s members were agreed with all the perception statements except that JFM activities helps in increasing the agriculture yield/land productivity, promotes forest tourism and helpful in improving communication skills of participants.